A legal study of migrant workers rights in Malaysia / Nur Anieza Anis Mohd Ariffin and Farah Hazwani Mohd Zulkufli - Mohd Ariffin, Nur Anieza Anis; Mohd Zulkufli, Farah Hazwani (Faculty of Law, 2016)
This study is carried out to identify the various forms of abuse of the rights of migrant workers in Malaysia, to examine whether the existing labour laws in Malaysia (Employment Act 1955, Industrial Relations Act 1967, Trade Unions Act 1959, Workmen Compensation Act 1952, Employee Provident Fund Act 1991, Occupational Safety and Health Act 1994, Immigration Act 1959 and Employment (Restriction) Act 1968) are adequate to protect the rights of migrant workers and final objective is to recommend changes in laws and policies that would provide better protection to migrant workers in Malaysia. Few interview conducted by Amnesty International and H.R. Watch in regards of abuses cases among migrant workers has been reviewed and were used to support the information. The data showed that existing law does not comprehensive enough to protect migrant workers on their rights in term of employment. This is because each of the Act has its own limitation and term that have been covered. Furthermore, most of the employers, agents and enforcement have violated the law. In fact in term of the enforcement of the law is weak. Thus authority is recommended to have specific Act that could protect migrant workers and improvise the protection.